UD-WCMA: An energy estimation and forecast scheme for solar powered wireless sensor networks. (15th July 2017) - Dehwah, Ahmad H.; Elmetennani, Shahrazed; Claudel, Christian
Abstract: Energy estimation and forecast represents an important role for energy management in solar-powered wireless sensor networks (WSNs). In general, the energy in such networks is managed over a finite time horizon in the future based on input solar power forecasts to enable continuous operation of the WSNs and achieve the sensing objectives while ensuring that no node runs out of energy. In this article, we propose a dynamic version of the weather conditioned moving average technique (UD-WCMA) to estimate and predict the variations of the solar power in a wireless sensor network. The presented approach combines the information from the real-time measurement data and a set of stored profiles representing the energy patterns in the WSNs location to update the prediction model. The UD-WCMA scheme is based on adaptive weighting parameters depending on the weather changes which makes it flexible compared to the existing estimation schemes without any precalibration. A performance analysis has been performed considering real irradiance profiles to assess the UD-WCMA prediction accuracy. Comparative numerical tests to standard forecasting schemes (EWMA, WCMA, and Pro-Energy) shows the outperformance of the new algorithm. The experimental validation has proven the interesting features of the UD-WCMA in real time low power sensor nodes. Highlights: Introducing a new dynamical version of the (WCMA) forecast scheme. Proposing a new dynamical forecast scheme with adaptive parameters. The new proposed scheme adapts to the current day dynamics with minimal training. The new proposed scheme is validated using real data (weather station and WSN). Validation shows the outperformance of our scheme compared to existing schemes.